Effects of multi-wavelength ultraviolet radiation on the inactivation and reactivation of Escherichia coli in recirculating water system - Weixiao Zhang; Wenyu Zhao; Yuxin Sun; Yan Sun; Baolong Wang; Mingyuan Liu; Zhujun Qiu; Yuqing Wang; Ziyi Sun; Peifen Hu; Qian Zhang; Ying Liu (Aquaculture Reports)
Ultraviolet (UV) disinfection plays a crucial role in controlling large-scale outbreaks disease in aquaculture. As a safe and efficient new light source, ultraviolet light-emitting diode (UV-LED) can combine specific wavelengths. The effects of the combination of UVC-LED (275 nm) and UVA-LED (365 nm) on the elimination and reactivation of Escherichia coli (E. coli) were investigated in this study. The results showed that UVC-LED could effectively inactivate E. coli, while UVA-LED had a limited effect E. coli removal. The inactivation of bacteria increased with the UVC-LED dose. It was found that UVA-LED pre-treatment improved the removal of E. coli in the combined treatment. The combination of UVA-LED followed by UVC-LED irradiation exhibited a synergistic effect. UVA irradiation at 3240 mJ/cm2 followed by 750 mJ/cm2 UVC irradiation resulted in a 3.18 log inactivation, which was about 2 log higher than that achieved by 750 mJ/cm2 UVC irradiation alone. Following disinfection, E. coli exhibited reactivation, with the dark repair rate exceeding that of photoreactivation. The bacterial reactivation rate increased with duration after UVC irradiation. High dose sequential UVA-UVC irradiation can effectively inhibit bacterial reactivation, delaying the reactivation. After 3240 mJ/cm2 UVA followed by 750 mJ/cm2 UVC irradiation, the dark repair rate of E. coli reached a minimum of 193.81 ± 5.85 % at 72 h. This study revealed the effective inactivation of bacteria through the combination of UVA-LED and UVC-LED, clarifying the mechanisms and influencing factors associated with inactivation and reactivation during UV synergistic disinfection. Simulate the actual water treatment process more realistically. And the bacterial reactivation can be effectively inhibited by high-dose UV irradiation and avoidance of visible light after irradiation. Our findings provide valuable insights for the design and operation of UV disinfection in recirculating aquaculture, it also clearly presenting the challenges in the actual water treatment process.